Promoting healthy foods among urban school children in Bangladesh: a qualitative inquiry of the challenges and opportunities - A. M. Rumayan Hasan; George Smith; Md Harunor Rashid; Mohammad Abdus Selim; Sabrina Rasheed (BMC, 2021)
Abstract Background In Bangladesh overweight and obesity among urban school children are on the rise. Urban school children tend to consume foods dense in calories and few fruits and vegetables which is associated with overweight and obesity. The current study explored the barriers and opportunities for promoting healthy diets among school children from the perspective of teachers and parents in Dhaka, Bangladesh. Methods We conducted 14 key informant interviews with teachers and principals, six focus group discussions with 31 mothers of school children (5 to 15 year old) and 14 structured observations of the school food environment. Inductive thematic analysis was performed manually. Results Schools were important for development of food preferences of children, however, most school cafeterias provided foods based on profit rather than health considerations. A shift in food culture resulted in making eating out acquire many meanings beyond convenience. Mothers, especially those who were employed, struggled to prepare healthy foods due to time pressure. Mothers were generally concerned about chemicals added to raw foods in markets which led to limited fruit and vegetable consumption. Conclusions There were many challenges to promoting healthy foods to school children within and outside the school. It is important to formulate policies and guidance to create a supportive environment for healthy foods in and in the proximity of schools. It is also important to educate consumers about identifying and choosing healthy foods. Laws related to food safety should be adequately implemented to boost the population's confidence in safety of available healthy foods in the food system.